Post‑discharge spirometry evaluation in patients recovering from moderate‑to‑critical COVID‑19 : a cross‑sectional study - Chai, Chee Shee; MuhammadAmin, Ibrahim; NurAmira, Azhar; Zulaika, Roslan; Rozila, Harun; Swarna Lata, Krishnabahawan; Aruna A. P., Karthigayan; Roqiah Fatmawati, Abdul Kadir; Busra, Johari; Diana Ng, Leh Ching; Benedict Sim, Lim Heng; Lim, Chong Kin; et al. (Springer Nature, 2024)
Understanding the prevalence of abnormal lung function and its associated factors among patients recovering from COVID-19 is crucial for enhancing post-COVID care strategies. This study primarily aimed to determine the prevalence and types of spirometry abnormalities among post-COVID-19 patients in Malaysia, with a secondary objective of identifying its associated factors. Conducted at the COVID-19 Research Clinic, Faculty of Medicine, University Technology MARA, from March 2021 to December 2022, this study included patients at least three months post-discharge from hospitals following moderate-to-critical COVID-19. Of 408 patients studied, abnormal spirometry was found in 46.8%, with 28.4% exhibiting a restrictive pattern, 17.4% showing preserved ratio impaired spirometry (PRISm), and 1.0% displaying an obstructive pattern. Factors independently associated with abnormal spirometry included consolidation on chest X-ray (OR 8.1, 95% CI 1.75–37.42, p = 0.008), underlying cardiovascular disease (OR 3.5, 95% CI 1.19–10.47, p = 0.023), ground-glass opacity on chest X-ray (OR 2.6, 95% CI 1.52–4.30, p < 0.001), and oxygen desaturation during the 6-min walk test (OR 1.9, 95% CI 1.20–3.06, p = 0.007). This study highlights that patients recovering from moderate-to-critical COVID-19 often exhibit abnormal spirometry, notably a restrictive pattern and PRISm. Routine spirometry screening for high-risk patients is recommended.